Coronary spasm as the cause of myocardial ischaemia in a patient with anomalous origin of the left anterior descending artery from the proximal right coronary artery. (11th June 2014) - Nakazato, Jun; Hirata, Kazuhito; Wake, Minoru
Abstract : A 49-year-old woman developed angina at rest. A CT of the coronary artery revealed that the left anterior descending artery arose from the right coronary artery, and traversed between the aorta and pulmonary trunk. An exercise stress myocardial scintigraphy did not reproduce myocardial ischaemia or anginal symptoms. A coronary angiography did not show any atherosclerotic changes. Finally, an ergotamine provocation test for vasospasm revealed diffuse severe spasm in the right coronary artery and the left anterior descending artery. Surgical correction of the anomaly was deferred and the patient was managed with medications to control spasm with good clinical outcome.